Effects of Intraperitoneally Administered Folic Acid on the Healing of Repaired Tibial Nerves in Rats - Harma, Ahmet; Sahin, Mehmet Sukru; Zorludemir, Suzan (Journal of Reconstructive Microsurgery, 2015)
Background Complete nerve regeneration and clinical healing remain a challenge despite considerable advances in the treatment of peripheral nerve injuries. To improve nerve regeneration, several experimental molecular procedures have been attempted. This study aimed to investigate the effects of folic acid on peripheral nerve healing after transection and end-to-end suture repair of the tibial nerve in rats.Methods In this study, 20 adult male Wistar Albino rats weighing 225 to 250 g were used. The right tibial nerves of 20 rats were explored, transected, and sutured using the end-to-end technique. The rats were randomly allocated to either the intraperitoneally administered folic acid group (test group) or the control group. Preoperative and 6-week postoperative neurophysiological studies were performed by the same researcher. Myelin-sheathed axons were counted.Results The results demonstrated that the folic acid–treated group exhibited improved electromyographic results compared with the control group. Histological evaluation revealed that the axons were well preserved and that the axon quantity and density were increased in the test group compared with the control group. Quantitative results also increased in the test group compared with the control group (p = 0.001).Conclusion In this study, 6-week intraperitoneal administration of 80 µg/kg of folic acid significantly improved peripheral nerve healing. Histological analysis of the group that received folic acid revealed increased axon myelination with little granular tissue or fibrosis. We propose that folic acid supplementation may be an effective component of peripheral nerve injury treatment.
Keywords: folic acid; peripheral nerve; nerve repair; regeneration